An overview of carbothermal synthesis of metal–biochar composites for the removal of oxyanion contaminants from aqueous solution. (April 2018) - Li, Ronghua; Wang, Jim J.; Gaston, Lewis A.; Zhou, Baoyue; Li, Manlin; Xiao, Ran; Wang, Quan; Zhang, Zengqiang; Huang, Hui; Liang, Wen; Huang, Heteng; Zhang, Xiaofeng
Abstract: Biochar shows promise as a potential low–cost sorbent for removing oxyanions from wastewater. However, this generic material exhibits a very wide range in porosity, surface area and surface chemical properties that depend on the starting biomass composition and the conditions under which it is converted to char. Without dosing either reactant biomass or product biochar with certain metals (in elemental, oxide/hydroxide or layered double hydroxide form), the capacity of biochar to remove oxyanions is usually low. This review compiles the recent research on modifications of biochar to produce metal-biochar composites that exhibit high oxyanion removal capacities. The general effect of the added metal is first established and then an overview of the several syntheses used to make metal–biochar composites is presented. Effects of chemical activation and of the addition of single metallic elements, single and binary oxides/hydroxides, and layered double hydroxides on removal of AsO4 3–, AsO3 3–, CrO4 2–, NO3 − and PO4 3– are next summarized. The effects of metal dosing and pyrolysis conditions on the surface chemistry and environmental stability of the composite are discussed. Finally, a summary of the research needed to maximize and/or target removal of specific oxyanions, address issues of long–term ecotoxicity of metal–biochar composites, and verify performance with field-testing is presented. Graphical abstract: Image